Drying kinetics of natural and parchment coffee at low temperature and relative humidity using a heat pump (Research, Society and Development, 2020)
The objective of this work was to evaluate the drying kinetics of natural and parchment coffee beans and to fit mathematical models to experimental data using a heat pump prototype. The scientific methodology used in this experiment was a research at the laboratory level using the quantitative method. The coffee beans were pre-dried on a suspended terrace and, when they reached the initial average moisture content of 35.20 and 44.87% (wet basis), for natural and parchment coffee, respectively, they were sent for drying in the prototype of a heat pump drying system. The drying was carried out in a fixed layer, with 900 g of natural coffee and 700 g of parchment coffee. Drying was carried out under four conditions of dry bulb temperature, dew point temperature and relative humidity, in a completely randomized design, in three replications. From the determination of the humidity ratio, different mathematical models were adjusted to describe the drying kinetics of coffee beans. The drying time of natural and parchment coffee using the heat pump system can be considered low for all drying conditions,given the morphological characteristics and the high initial moisture content of the product. The Midilli model satisfactorily described the drying kinetics of naturaland parchment coffee atlow temperature, using the heat pump system. The drying rate is higher for the highest temperatures only in the initial phase of the process.